Music theatre: at the crest of music education's third wave. Issue 4 (2nd October 2015) - Legg, Robert; Green, Alex
Abstract : In the United Kingdom, curricular music education has seen two main waves of development and is in the process of shaping a third. Ideas from the second wave have maintained theoretical dominance to the present day, despite the concerns expressed by some about their practical implementation. This paper suggests that problems with the implementation of second‐wave ideas have been caused by hermeneutic complexities inherent to the word 'music' as well as by an ongoing ideological debate about the proper purpose of music education. It is proposed here that by approaching musical learning in the emergent third wave through the sub‐discipline of 'music theatre' – and by conceiving that term in its broadest sense – this interpretive difficulty can be avoided whilst many practical advantages may be reaped. The notion of music theatre as a key component of music education's third wave is explored alongside its theoretical prerequisites, and a number of questions are identified for further consideration.